Student’s Perspectives on the Utilization of the Word Box Application to Enhance Speaking Skills for Junior High School Students - Sarwandi Kasmei; Deasy Yunita Siregar (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
The phenomenon demonstrates how traditional practices are making it difficult for Indonesian junior high students to speak English. Following its release, the Word Box app garnered praise for its interactive features and pronunciation, which boosted students' vocabulary and self-esteem. However, problems with internet access and a lack of conversational practice surfaced, suggesting that the software works well as an additional tool that has to be integrated with large programs. The purpose of this study was to investigate the viewpoints of junior high school students about using the Word Box application to improve their English speaking abilities, paying particular attention to usability, efficacy, perceived advantages and difficulties, and how student views affect participation in speaking exercises. Purposive sampling was used to select 28 junior high school students as participants in a qualitative case study approach. Data were collected through semi-structured interviews with 12 students providing detailed responses and questionnaires distributed a total of 28 student via Google Forms. Thematic analysis based on Braun and Clarke's (2006) framework was used to analyze the data. Students' perspective of the Word Box application's usefulness and efficiency were largely favorable. Important results showed that 92.86% of users thought the program enhanced their ability to speak English, and 82.14% of participants thought the application's accessibility and user interface were good. The contextual examples, interactive video/film clip system, and audio pronunciation feature were really appreciated by the students 92.86%. Therefore, this study comes to the conclusion that Word Box applications might be taken into consideration as well as well-targerted utilization tactics.